Analisis Makna dan Nilai Nilai Moral Pada Puisi Anak Usia Sekolah Dasar dengan Tema Lingkungan - Kinasih, Arum; Exa, Hasna Nabila; Amalia, Siva Anisa; Yulisetiyani, Septi (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
The author chose the topic of analyzing meaning and moral values ​​so that elementary school age students can easily absorb the meaning and understand the moral values ​​contained in children's poetry so that they can be implemented in everyday life. The author took samples of 6 poems on the poindua.net website by Yunita. The method used by the author is the literary study method with data analysis techniques in the form of interactive analysis. The results of the analysis carried out by the author show that children's poetry has several implied meanings so it is difficult to understand and contains moral values ​​in it. One of the results of the poem that we analyzed was entitled "Rainbow" with the moral value contained, namely being grateful for all the blessings that God has given us.